Gene-Environment Interaction in the Determination of Levels of Plasma Fibrinogen - Humphries, Steve E.; Luong, Le-Anh; Montgomery, Hugh E.; Day, Ian N.M.; Mohamed-Ali, Vidya; Yudkin, John S. (Thrombosis and Haemostasis, 1999)
This review will focus on the inflammatory risk factors that may influence changes in plasma fibrinogen levels and that may influence an individual’s risk of ischemic heart disease (IHD). These inflammatory risk factors occur to a different extent in individuals as their environment changes. Although a specific genotype may be associated, in healthy subjects, with modest differences in levels of a risk factor for thrombosis, this effect may be larger or smaller in subgroups of subjects. Documenting such gene-environment interactions is important if genotype information is ever to be used in a clinical or diagnostic setting. Understanding the molecular mechanisms of such interactions is vital to the development of novel therapeutic approaches to reduce risk of myocardial infarction (MI).We review some of the gene-environment interactions detected to date for the G-455A β-fibrinogen gene promoter polymorphism. Carriers of the A allele, representing roughly 20% of the population, consistently have, on average, 7% to 10% higher fibrinogen levels than those with the genotype GG. Data will be presented to demonstrate interaction between situations of inflammatory stimulation (e.g., smoking habit, presence of ischemic disease, and level of physical exercise) in the determination of the magnitude of the effect of the A allele on plasma fibrinogen levels.The cytokine interleukin-6 (IL-6) is the likely link between inflammatory processes and IHD. Recently we have identified a functional G/C polymorphism at -174bp in the IL-6 promoter, with the G allele being a 2 to 4 times stronger promoter upon stimulation with interleukin-1 (IL-1) or lipopolysaccharide (LPS). In a small study of healthy subjects, the C allele was associated with significantly lower mean plasma levels of IL-6, an effect which may be protect against the development of IHD. Finally, we describe a rapid throughput genotyping method that is useful for large-scale genetic epidemiology studies.